2022
DOI: 10.1021/acsphotonics.2c01389
|View full text |Cite
|
Sign up to set email alerts
|

Passive Radiative Cooling of Silicon Solar Modules with Photonic Silica Microcylinders

Abstract: Passive radiative cooling is a method to dissipate excess heat from a material by the spontaneous emission of infrared thermal radiation. For a solar cell, the challenge is to enhance PRC while retaining transparency for sunlight above the bandgap. Here, we design a hexagonal array of cylinders etched into the top surface of silica solar module glass to enhance passive radiative cooling. Multipolar Mie-like resonances in the cylinders are shown to cause antireflection effects in the infrared, which results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For example, soda-lime glass and borosilicate glass are two common types of glass that are made with SiO 2 as their principal component, but they differ in their composition of added minerals and impurities, which results in variations of the optical properties. While fused silica is highly reflective in the atmospheric window region (≈70%), the added impurities in soda [ 54] Experimental 7 --Zhang et al ( 2019) [ 55] Experimental ---Ishii et al (2020) [ 56] Experimental 5.9 0.85 -Zhao et al (2019) [ 36] Silica fibers Numerical --178 Yalçın R A et al (2020) [ 57] Experimental 6.0 0.90 112 Tsai et al (2023) [ 28] 1D gratings Numerical 31.4 --Zhu et al ( 2013) [ 58] Numerical --114 Blandre et al (2020) [ 59] Numerical -> 0.90 98 Liu et al ( 2021) [ 60] Experimental 3.6 0.91 -Zhao et al (2022) [ 61] 2D micropatterns Experimental 13 --Zhu et al (2015) [ 62] Experimental 2 -600 Long et al (2019) [ 63] Numerical 9 ≈1.0 121 Li et al (2022) [ 64] Experimental 7 0.952 -Pinto et al ( 2023) [ 52] Numerical 17.6 ≈1.0 -Zhu et al ( 2014) [ 45] Experimental -> 0.96 -Lu et al (2017) [ 65] Experimental 9.2 > 0.98 -Fathabadi et al ( 2021) [ 38] Experimental 3 0.977 -Akerboom et al (2022) [ 39] Experimental 7.1 0.95 143 Ding et al (2022) [ 37] Experimental -0.947 -Arrés Chillón et al (2022) [ 66] Microspheres Experimental -> 0.94 -Atiganyanun et al (2018) [ 67] Experimental ≈6.9 --Fan et al (2020) [ 68] Numerical 73 --Whitworth et al (2021) [ 53] Experimental 19 >0.98 350 Fernandez et al (2019) [ 40] Experimental 5 0.946 -Lin et al (2022) [ 69] Numerical -0.916 80 Chen et al (2021) [ 70] lime glass reduce the reflectance in the reststrahlen band resulting in a relatively lower reflectance in the desired region (≈30%), compared to that of pure fused-SiO 2 . Various photonic techniques also have been utilized to enhance th...…”
Section: Basic Properties Of Sio 2 -Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, soda-lime glass and borosilicate glass are two common types of glass that are made with SiO 2 as their principal component, but they differ in their composition of added minerals and impurities, which results in variations of the optical properties. While fused silica is highly reflective in the atmospheric window region (≈70%), the added impurities in soda [ 54] Experimental 7 --Zhang et al ( 2019) [ 55] Experimental ---Ishii et al (2020) [ 56] Experimental 5.9 0.85 -Zhao et al (2019) [ 36] Silica fibers Numerical --178 Yalçın R A et al (2020) [ 57] Experimental 6.0 0.90 112 Tsai et al (2023) [ 28] 1D gratings Numerical 31.4 --Zhu et al ( 2013) [ 58] Numerical --114 Blandre et al (2020) [ 59] Numerical -> 0.90 98 Liu et al ( 2021) [ 60] Experimental 3.6 0.91 -Zhao et al (2022) [ 61] 2D micropatterns Experimental 13 --Zhu et al (2015) [ 62] Experimental 2 -600 Long et al (2019) [ 63] Numerical 9 ≈1.0 121 Li et al (2022) [ 64] Experimental 7 0.952 -Pinto et al ( 2023) [ 52] Numerical 17.6 ≈1.0 -Zhu et al ( 2014) [ 45] Experimental -> 0.96 -Lu et al (2017) [ 65] Experimental 9.2 > 0.98 -Fathabadi et al ( 2021) [ 38] Experimental 3 0.977 -Akerboom et al (2022) [ 39] Experimental 7.1 0.95 143 Ding et al (2022) [ 37] Experimental -0.947 -Arrés Chillón et al (2022) [ 66] Microspheres Experimental -> 0.94 -Atiganyanun et al (2018) [ 67] Experimental ≈6.9 --Fan et al (2020) [ 68] Numerical 73 --Whitworth et al (2021) [ 53] Experimental 19 >0.98 350 Fernandez et al (2019) [ 40] Experimental 5 0.946 -Lin et al (2022) [ 69] Numerical -0.916 80 Chen et al (2021) [ 70] lime glass reduce the reflectance in the reststrahlen band resulting in a relatively lower reflectance in the desired region (≈30%), compared to that of pure fused-SiO 2 . Various photonic techniques also have been utilized to enhance th...…”
Section: Basic Properties Of Sio 2 -Based Materialsmentioning
confidence: 99%
“…Combined with Equation 1, the overall net cooling power obtained shows a direct proportionality with infrared emissivity. By considering a set of representative values of the average emissivity in the atmospheric transparency window ranging from the bulk case to the highest value reported obtained experimentally in the literature for a SiO 2 emitter (𝜖 avg = 0.98 [38][39][40] ), we see that the expected temperature drop can potentially increase from 5.3 °C to 8.8 °C, with a corresponding net cooling power enhancement of more than 27 W m −2 (Figure 2 and Table 1). How to achieve such high average emissivity values in practice for SiO 2 emitters and hence take full advantage of this additional net cooling power will be the main subject of this review.…”
Section: Fundamentals Of Radiative Sky Coolingmentioning
confidence: 99%
“…Spectrum regulation has been widely employed in photovoltaic light and thermal management. [32,[53][54][55][56] Generally, transparent coatings can be facilely processed on photovoltaic panels, which can enhance the transmittance of solar radiation and simultaneously improve thermal infrared emission. The enhanced solar transmittance, especially in the bandgap can substantially reduce light loss and improve the photocurrent intensity of photovoltaic panels.…”
Section: Working Principles Of Passive Photovoltaic Coolingmentioning
confidence: 99%
“…Therefore, some researchers doubt the necessity of developing a novel radiative cooling cover for photovoltaic cooling. [127] However, some reports have revealed that photovoltaic glass covers generally present the infrared emissivity valley in the atmospheric window (8-13 μm), [28,54,128] which has some impact on photovoltaic cooling performance. Moreover, their moderate solar transmittance also places some restrictions on the performance improvement of photovoltaic panels in the actual environment.…”
Section: Radiative Coolingmentioning
confidence: 99%
See 1 more Smart Citation